The Effect of Pelargonium endlicherianum Fenzl. root extracts on formation of nanoparticles and their antimicrobial activities - Karatoprak, Gokce Seker; Aydin, Gamze; Altinsoy, Berrak; Altinkaynak, Cevahir; Kosar, Muberra; Ocsoy, Ismail (Elsevier Science Inc, 2017)
Herein, we report the biosynthesis of Ag NPs, for the first time, using identified antimicrobial molecules (gallic acid + apocynin) and (gallic acid + apocynin+ quercetin) from the medicinal plant Pelargonium endlicherianum Fenzl. and dramatically enhanced antimicrobial activity. We also investigate the role of each molecule on formation Ag NPs and explain the increase in the antimicrobial activity of identified molecules mediated Ag NPs. The extraction protocols, 11% ethanol and 70% methanol, resulted in identification of different constituents of gallic acid + apotynin (M1) and gallit acid + apocynin+ quercetin (M2) with respective concentrations. The M1-Ag and M2-Ag NPs exhibit excellent inhibitory activities towards Gram negative bacteria; Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 and Gram positive bacteria; Staphylococcus epidermidis ATCC 3699 bacterial using in vitro microdilution method. The minimum inhibitory concentration (MIC) values of M1-Ag and M2-Ag NPs were determined to be 7.81 and 6.25 ppm for S. epidermidis, respectively. Surprisingly, MIC value for both Ag NPs was indicated to be identical as 9.37 ppm for P. aeruginosa and E., coli. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Pelargonium endlicherianum; Silver nanoparticle; Antimicrobial activity